Factors Predicting Survival in Ruptured Hepatocellular Carcinoma Treated with Surgical Resection - Assawasirisin C. (2023)
Objective: Today, ruptured hepatocellular carcinoma (HCC) is a less frequently encountered problem globally due to availability of cancer surveillance protocols for the high-risk population. However, in Thailand, a number of patients do not enroll in screening programs, leading to high rates of ruptured complications. In fit-for-surgery and clinically stable patients, hepatectomy means long-term survival. This study aimed to identify predictive factors of survival in resected patients. Materials and Methods: A retrospective review of patients with ruptured HCC who underwent liver resection between January 2013 and December 2019 at Siriraj Hospital was performed. The clinical data and outcomes of patients was analyzed. Results: A total of forty-two patients with ruptured HCC underwent resection or 9.8% of all operable HCC cases. There were 6 patients (14.3%) who suffered from postoperative liver failure and one patient (2.4%) died within 30 days. Overall survival (OS) and recurrence-free survival (RFS) were 90%, 64%, 52% and 42.5%, 24%, 16% at 1, 3, and 5 years, respectively. The factors affecting OS were tumor size >10 cm, vascular invasion, and positive resection margin. Conclusion: Surgical resection in ruptured HCC provides long-term survival. Predicting factors affecting overall survival were large tumor size, vascular invasion, and positive resection margin. Patient selection is a key for better patient's outcomes.